Secession and the political economy of South Sudan from 2011 to 2017 - Chilunjika, Alouis; Daky, Dhowoch Orozu Lokine; Chilunjika - Muzvidziwa, Sharon R.T (Taylor and Francis, 2021)
In the quest to become autonomous, southern Sudan opted for secession from northern Sudan in 2011. Among other reasons, the major cause for this secession was to redress the imbalances perpetrated by the Arab minority, who discriminated against the people of the southern part of Sudan. The chief aim of this study was to assess the impact of secession from Sudan on the political economy of South Sudan in the period 2011–2017. The field research was conducted in South Sudan, Juba district, focusing on the surrounding areas of Munuki, Amarat, Sherikhat, Nyakuron, and Thongpiny. The study embraced blended decolonial research methods for data gathering. Techniques such as questionnaires and interviews were utilised. The authors discovered that the secession has had a negative impact on the political economy of South Sudan, as the newly founded state has been affected by the syndrome of dependence on its former parent state (Sudan), which creates perpetual problems. The research findings lead to the conclusion that for secession to have a positive impact on the political economy of African nations, robust institutions should be established soon after secession, there should be equality among ethnic groups, and sound policies should be established to stimulate their economies.